3 - Développement de l’orpaillage et mutations dans les villages aurifères du sud-est du Sénégal - Doucouré, Bakary (Africa Development, 2021)
In south-eastern Senegal, namely the Kedougou region, the increasing development of gold panning from the 2000s has led to many changes in auriferous villages and gold panning areas. These changes are of social, demographic, political, economic and environmental nature. This paper focuses on the analysis of changes and their multiple implications on the lives of individuals, groups and communities, as well as the environment, micro-economies and the socio-political organization of villages and areas concerned. It ultimately shows that so far gold panning has rather resulted in a problematic development leading to the “multidimensional phagedena” phenomenon, that is to say the tendency to spreading, deepening and worsening problems at social, economic, environmental levels, etc.